2003
DOI: 10.1016/s0378-1097(02)01142-4
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar system of ungerminated Colletotrichum graminicola conidia: convergence of autophagic and endocytic pathways

Abstract: Vacuoles of ungerminated Colletotrichum graminicola conidia engulf cytoplasmic structures by a process analogous to microautophagy, demonstrated by using a vacuolar membrane acid phosphatase marker. Fusion of vesicles with vacuoles, without deposition of the acid phosphatase reaction product has been observed, suggesting other pathways of material delivery to vacuoles than microautophagy. Plasma membrane invaginations, multivesicular bodies and retention of neutral red into small vesicles, which were internali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…1,2 There are now several examples in eukaryotic organisms, which show the involvement of autophagic type II programmed cell death in stress-induced cellular differentiation and development, such as ascospore differentiation in Saccharomyces cerevisiae, the production of a multicellular stage upon nutrient deprivation in the slime-mold Dictyostelium discoidum and the formation of the dauer larvae in the nematode Caenorhabditis elegans. 4 Involvement of the appressorial vacuole as a dynamic cellular compartment during infection-related development had in fact already been suggested in the fungal pathogens Colletotrichum gloeosporioides and M. grisea previously, 5,6 but our study has provided but our study has provided study has provided evidence that autophagy in M. grisea has a causative role in spore collapse and cell death, and is a necessary prerequisite for successful infection of plant tissue through the differentiation of a fully functional appressorium. This result is in contrast with findings in the filamentous fungus Podospora anserina that have indicated that autophagy does not play a causal role in programmed cell death during fungal vegetative incompatibility, 7 but is consistent with studies in mammalian cells showing that ATG genes can promote programmed cell death by autophagy.…”
Section: Introductionmentioning
confidence: 59%
“…1,2 There are now several examples in eukaryotic organisms, which show the involvement of autophagic type II programmed cell death in stress-induced cellular differentiation and development, such as ascospore differentiation in Saccharomyces cerevisiae, the production of a multicellular stage upon nutrient deprivation in the slime-mold Dictyostelium discoidum and the formation of the dauer larvae in the nematode Caenorhabditis elegans. 4 Involvement of the appressorial vacuole as a dynamic cellular compartment during infection-related development had in fact already been suggested in the fungal pathogens Colletotrichum gloeosporioides and M. grisea previously, 5,6 but our study has provided but our study has provided study has provided evidence that autophagy in M. grisea has a causative role in spore collapse and cell death, and is a necessary prerequisite for successful infection of plant tissue through the differentiation of a fully functional appressorium. This result is in contrast with findings in the filamentous fungus Podospora anserina that have indicated that autophagy does not play a causal role in programmed cell death during fungal vegetative incompatibility, 7 but is consistent with studies in mammalian cells showing that ATG genes can promote programmed cell death by autophagy.…”
Section: Introductionmentioning
confidence: 59%
“…Neutral red is a weak cationic dye that penetrates cells by nonionic diffusion and is compartmentalized by living cells in a process requiring cellular energy. This dye has been used as a cell viability indicator in mammalian cells [14], [15] and for the identification of lysosomes and vesicles in fungal species such as Cryptococcus neoformans , Colletotrichum graminicola and Botrytis cinerea [16], [17], [18]. In control experiments, we observed that conidia capable of compartmentalizing the dye were able to germinate and develop into hyphae (Fig.1A,B) whereas conidia that failed to compartmentalize the dye did not germinate (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…A microscopic assay was developed to determine the viability of individual conidia internalized by host cells. Neutral red, a vital dye that requires cellular energy for active uptake was used as a viability indicator [14], [15], [16], [17], [18]. First, however, control experiments were performed to ascertain the viability of conidia that displayed different staining patterns of the neutral red dye.…”
Section: Methodsmentioning
confidence: 99%
“…Taken together, it is apparent that EGFP-AoVam3p localizes on late endosomes/prevacuolar compartments in addition to vacuoles. Exploration for possible candidates of late endosome/prevacuolar compartment-resident proteins will be (32). Further investigations of possible roles of vacuoles (e.g., storage degradation and cell expansion) may help us to understand the mechanism of conidial germination in filamentous fungi.…”
Section: Discussionmentioning
confidence: 99%